Impacts of large-scale investments in agriculture to water resources, ecosystems and livelihoods, and development of policy options [Abstract only] - Hoa, E.; Chiramba, T.; Williams, Timothy O. (2014)
ntroduction and objectives: As water availability is a strong driver for the acquisition of agricultural land, the implementation of foreign direct investments in land has also been described as “water grabbing” with severe impact to water and related ecosystems, creating water scarcity and impoverishing local population. The objective is to better understand the impacts of large-scale investments in agriculture to water resources, ecosystems and livelihoods, and to develop policy options for decision-makers for leasing agricultural land without compromising ecosystem services and ensuring equitable benefits including to the affected communities.Methodology approach: As a significant share of a country’s water resources may be used in these land deals, some policy options on land and water acquisition by large-scale investors would ensure that such investments promote food and water security without compromising local and downstream water availability and quality. Legal, political, socio-economic and environmental dimensions of large-scale land deals need to be further investigated to help decision-makers implement beneficial measures and formulate policies and programmes that ensure a wider distribution of such benefits.Analysis, results, conclusions and recommendation: The presentation will showcase :